Pleomorphic adenoma: the great mimicker of malignancy - Hernandez-Prera, Juan C; Skálová, Alena; Franchi, Alessandro; Rinaldo, Alessandra; Vander Poorten, Vincent; Zbären, Peter; Ferlito, Alfio; Wenig, Bruce M (Histopathology, 2021)
Pleomorphic adenoma (PA) is the most common salivary gland neoplasm, and its diagnosis is straightforward in the majority of cases. However, not infrequently, PA shows unusual and uncommon histological features that can be confused with those of malignancy. The difficulties in diagnosing PA arise from its ability to mimic invasion, show atypical or metaplastic cytomorphology, and show morphological features that overlap with those of established salivary gland carcinomas. In addition, recognising early malignant transformation to carcinoma ex-pleomorphic adenoma continues to be a frequent challenge. This review describes the diagnostic pitfalls of PA, and offers a systematic approach to avoid them by combining classic histopathology with novel immunohistochemical and molecular tests.
Keywords: diferenciální diagnóza; squamous metaplasia; MAML2; nádory slinných žláz; Adenoma, Pleomorphic; oncocytic metaplasia; MYB; adenokarcinom; metaplazie; early carcinoma ex pleomorphic adenoma; invasion; Biomarkers, Tumor; Carcinoma; pleomorphic adenoma; nádorové biomarkery; Humans; pleomorfní adenom; Metaplasia; Salivary Gland Neoplasms; Diagnosis, Differential; nádorová transformace buněk; PLAG1; Cell Transformation, Neoplastic; Adenocarcinoma; lidé; karcinom